Genetic factors related to the immune system in subjects at risk of developing Alzheimer's disease - Prendecki, Michał; Kowalska, Marta; Łagan-Jędrzejczyk, Urszula; Piekut, Thomas; Krokos, Aleksandra; Kozubski, Wojciech; Dorszewska, Jolanta (Journal of integrative neuroscience, 2020)
Alzheimer’s disease is the most common neurodegenerative disease and the cause of dementia. Although the pathomechanisms underlying Alzheimer’s disease have not been fully elucidated, there is evidence that genetic and environmental factors contribute to its development. Immune system changes, both environmentally-induced and, as a result of predisposing genetics, are implicated in Alzheimer’s disease etiopathogenesis. Genes associated with immune system dysfunction in Alzheimer’s disease include CLU, BIN1, CR1, ABCA7, HLA-DRB1, TREM2, EPHA1, and CD2AP. In particular, BIN1 and CLU, aberrations in which are thought to promote neurodegeneration by dysregulating exocytosis and immune processes, together with the E4 variant of the APOE gene, are among the most common genetic risk factors for Alzheimer’s disease. While the relationships between these genes in Alzheimer’s disease have been examined, little information exists regarding their role as variables predisposing first or second-degree relatives of Alzheimer’s disease patients to the illness. The rationale of this review is to suggest that individuals with a family history of Alzheimer’s disease who have the BIN1-T/T variant may be at significant risk of developing Alzheimer’s disease. Also, the unfavorable BIN1-T variant is independent of APOE E4-associated risk. People at risk of developing Alzheimer’s disease are more often carriers of the protective C-variant of the CLU gene, the presence of which might be associated with later-onset dementia observable within this high-risk group. It seems BIN1 and CLU together with, albeit independent of APOE E4, may be among the factors predisposing individuals with a family history of Alzheimer’s disease to developing the illness.